A load balancing algorithm for the parallel automated multilevel substructuring method. (December 2021) - Hyun, Cheolgyu; Lee, Phill-Seung
Highlights: A new load balancing algorithm for the parallel AMLS (PAMLS) method is presented. The proposed algorithm consists of two types of granularity. The computational efficiency of the original PAMLS method is considerably improved. Its performance is investigated through various numerical examples. Abstract: The objective of this paper is to present a load balancing algorithm for the parallel automated multilevel substructuring (PAMLS) method. In the PAMLS method, load balancing is highly dependent on the computation time for the transformation and back transformation procedures corresponding to substructures. To balance the workload among threads, the proposed algorithm consists of two types of granularity: coarse-grained and fine-grained parallel algorithms. According to the level of substructures, the coarse-grained parallel algorithm splits both the transformation and back transformation procedures and assigns them to threads. Through fine-grained parallelism, more threads are exploited for the transformation of each substructure compared to threads used in the original PAMLS method. Without repartitioning, the proposed algorithm significantly improves the efficiency of the PAMLS method.